Treatment of total edentulousness by fixed implant-supported prostheses - Alexandra-Elena Biculescu; Paolo Di Francesco; Mona Dardouk; Misu-Marian Babat; Ioana-Ana-Maria Ciorniciuc; Anca Iuliana Popescu (Romanian Journal of Stomatology)
Total edentulousness presents considerable obstacles to patients in terms of aesthetics, function, and general well-being [1]. Fixed implant-supported prostheses have emerged as a possible treatment option, providing more stability, comfort, and chewing efficiency than typical removable dentures [2]. To obtain predictable and effective outcomes, it is critical to use good case selection, detailed treatment planning, and interdisciplinary teamwork [3]. Considerations for bone quantity and quality, occlusal systems, and maintenance methods are also highlighted in order to maximize long-term prosthetic success and patient happiness [4]. This case report presents the interdisciplinary management of implant-prosthetic treatment and demonstrates the effectiveness of dental implants in the oral rehabilitation of completely edentulous patients, with a focus on the allon-six treatment approach.